Pengetahuan Anggaran dan Efektivitas Partisipasi dalam Hubungannya dengan Kepuasan atas Pelaksanaan Anggaran Kinerja - Anton Ryadi (Universitas Muhammadiyah Yogyakarta, Indonesia, 2007)
This research aim to examine the relationship of society knowledge about APBD, participate effectiveness in compilation of budgetary and satisfaction of performance budgetary implementation. This research is motivated by performance budgeting system regulation. Eksogen variable in this research is budgeting knowledge, while effectiveness participates and satisfaction of performance budgeting implementation represent endogen variables. The data in this research consist of primarily taken from questionnaires spread about 180 ones and the technical sampling by using judgment sampling. Hypothesis of this research are examine by using the path analysis that develop from regression model. The result in this research shows that lower participate effectiveness is caused by lowering understanding of society about budgetary. Satisfaction of performance budgetary implementation variable isn’t influenced by understanding of budgetary and participate effectiveness. The other alternative endogen variables are prosperity, good service and development equality.